EXPOSURE TO HEAT TREATMENT ON THE ENERGY SPECTRUM OF DEFECTS IN SILICON DOPED WITH MOLYBDENUM - Paluanova, A.D. (SCIENCE and SOCIETY, 2024)
The processes of the formation of defect centers in Si doped with molybdenum have been investigated using the methods of capacitive spectroscopy. It is shown that the diffusion introduction of molybdenum atoms into silicon leads to the formation of defect centers with deep levels EC–0.20 eV and EC–0.29 eV with electron capture cross sections n= 2·10-17 cm2 and n= 4·10-16 cm2 in n-Si. In the p-Si samples, one deep level with an ionization energy EV+0.35 eV and a hole capture cross section p= 7·10-15 cm2 was found.
Keywords: silicon; impurity; molybdenum; electron-neutral impurity; oxygen; carbon; defect formation